2009
DOI: 10.1016/s1470-2045(08)70340-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cells as prognostic markers in progressive, castration-resistant prostate cancer: a reanalysis of IMMC38 trial data

Abstract: SUMMARYBackground-To assess the use of circulating tumor cell (CTC) number as a continuous variable as a prognostic factor for survival, and for the clinical management of patients with progressive metastatic castration-resistant prostate cancer receiving first-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
466
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(486 citation statements)
references
References 23 publications
13
466
3
4
Order By: Relevance
“…Association of detection of !5 traditional CellSearch isolated CTCs/7.5 mL with poor prognosis in patients with advanced prostate cancer was initially reported around a decade ago (27)(28)(29) and has been recently further validated in several large-scaled clinical trials (30)(31)(32)(33). In our small patient cohort, we observed the associations of…”
Section: Discussionsupporting
confidence: 51%
“…Association of detection of !5 traditional CellSearch isolated CTCs/7.5 mL with poor prognosis in patients with advanced prostate cancer was initially reported around a decade ago (27)(28)(29) and has been recently further validated in several large-scaled clinical trials (30)(31)(32)(33). In our small patient cohort, we observed the associations of…”
Section: Discussionsupporting
confidence: 51%
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) have been shown to be an independent prognostic factor in metastatic breast cancer (MBC) [3][4][5][6], in metastatic prostate cancer [7][8][9][10] and in metastatic colorectal cancer [11,12]. They represent a promising tool for therapeutic monitoring: an elevated number of CTCs measured at any time in the clinical course were associated with a high likelihood of a very short time to progression.…”
Section: Introductionmentioning
confidence: 99%
“…surface-enhanced Raman spectroscopy biomarker | cancer cell identification | multiplexing | silver nanoparticles E arly and rapid identification of malignant cells [ideally freeflowing in biological fluids such as urine (1) or blood (2)(3)(4)] is a central goal in cancer research. Accordingly, seeking improvements in sensitivity and accuracy of detection and quantification through, for example, the development of cell-specific diagnostic tools and biomarkers is an active enterprise.…”
mentioning
confidence: 99%